RESPUESTA DE HÍBRIDOS DE CHILE ANAHEIM (CAPSICUM ANNUUM L.) CARDÓN Y 118, CULTIVADOS BAJO DOS SISTEMAS DE PRODUCCIÓN EN CONDICIONES DE INVERNADERO - León, José Jiménez; Elías, Jesús López; Huez López, Marco Antonio; García López, Alejandro Manelik; Soto Ortiz, Roberto; Escoboza García, Luis Fernando (European Scientific Journal, ESJ, 2014)
The production system under greenhouse makes possible to obtain higher yields and better fruit quality. Two Anaheim pepper hybrids were produced during summer-fall season of 2011 at the experimental field of the University of Sonora, México. The objectives were to evaluate the yield and fruit quality, and to determine the water use efficiency, under greenhouse conditions using two production systems, substrate and soil. In the soil system the higher fruit weights were obtained with 63.12 g fruit-1 and 61.98 g fruit-1, in Cardon and 118 respectively. The fruit number per plant and the yield in the first harvest were higher in the substrate system; however, the final averages were no significant among treatments. The higher fruit length, 17.52 and 15.52 cm in Cardon and 118 respectively, were obtained in the soil system. The fruit diameter did not present significant differences among treatments. The water use efficiency (WUE) was higher in the soil system, with 36.4 and 31.2 kg m-3 compared to 9.1 y 9.9 kg m-3 obtained in the substrate system for 118 and Cardon respectively.